A hardness prediction model considering grain size effect for ferrite steel. (2015) - Sun, Wenbo; Jin, Junsong; Wang, Xin-Yun
Hardness is frequently used as an index to evaluate the mechanical properties of manufactured parts. Prediction of hardness distribution is beneficial to the optimisation of process parameters. For polycrystalline materials, the grain size has significant influence on hardness. In this paper, a hardness prediction model for ferrite steel was established by taking the grain size effect into consideration. The influence of grain size and effective strain on the hardness evolution during cold forming processes was investigated based on both experiments and simulations. The results proved that initial hardness, hardness coefficient and hardening exponent are all significantly affected by the grain size, i.e., they all decrease with the increase in grain size. The model proposed was validated to be capable of predicting the hardness distribution in cold forgings with different initial grain sizes.